(3caGjI GdCUhds - (3GdNQGSGfj, GdCNhfO, eMeO cGXe, J (B1329 (3g`s
(3ChdgG (B:s
(3GdMeO ddg (B.. (3abO QJHJg Ydi ebOeI hebGUO hNGJeI CeG GdebOeI aaj HjGf CehQ GdChd Cf ehVhY cd Yde hgh GdPj jHMK ajg Yf YhGQVg GdPGJjI Cj HdG hGSWI aj GdYQhV gh faS ehVhYGJ eSGFdg (B...s
(3BNQgG (B:s
...(3hCeG UMI GdGdJRGe HeG COi Edjg ef GdCMcGe ef BKGQgG VQhQI Cf MLjI GdXf YbdG Ydi JbOjQ GdMcheI aj MGd GdGfSOGO dG jhLH UMJgG eY GdTc aj GdJbjO Hg (B..(3hbO GfbOM HeG PcQfG Cf GdUhGH(B..s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B7\ 11s
(3GdPQjYI (B18\ 810s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3CUhd Gdabgs